Effects of the ketogenic diet on multiple sclerosis with a focus on the paediatric population - Szponarowicz, Patrycja; Raczkiewicz, Przemysław; Rzeszutko, Mateusz; Snopkowski, Bartosz; Panek, Eliasz; Jasłowski, Damian; Panasiuk, Dominika; Korzec, Tomasz; Sosnowski, Jakub; Skrętowicz, Mateusz (Journal of Education, Health and Sport, 2023)
Introduction and Purpose: Multiple sclerosis (MS) is an autoimmune disease that damages the nervous system. Although MS is usually diagnosed in adults, it can also occur in children and adolescents, which presents diagnostic and therapeutic challenges. In recent years, attention has been drawn to the role of diet in alleviating MS symptoms, including in the pediatric population. The ketogenic diet, characterized by low carbohydrate intake, high fat intake, and moderate protein intake, is of interest as an additional therapeutic approach in MS due to its effects on metabolism and reduction of inflammation in the body. Materials and methods: This article reviews the literature on the impact of the ketogenic diet on MS, with particular emphasis on its impact on the course of MS in the pediatric population. Articles were searched by key words, e.g. multiple sclerosis, paediatrics, children, diet, ketogenic diet, in various configurations, in Scopus, Medline, Google Scholar databases. Current state of knowledge: While there are several studies on the effects of the ketogenic diet, including those on MS in children, the results are inconclusive and require further research. Some publications suggest that the ketogenic diet can help alleviate MS symptoms, such as problems with balance and coordination, and improve patients’ quality of life. Conclusions: In conclusion, the ketogenic diet may be a promising approach in the treatment of pediatric MS, but requires further research and careful assessment of benefits and risks before its introduction into therapy.